Effects of feeding regimes and early maturation on migratory behaviour of landlocked hatchery‐reared Atlantic salmon Salmo salar smolts. Issue 4 (October 2014) - Norrgård, J. R.; Bergman, E.; Schmitz, M.; Greenberg, L. A.
<x xml:space="preserve">Abstract</x> The migratory behaviour of hatchery‐reared landlocked Atlantic salmon Salmo salar raised under three different feeding regimes was monitored through the lower part of the River Klarälven, Sweden. The smolts were implanted with acoustic transmitters and released into the River Klarälven, 25 km upstream of the outlet in Lake Vänern. Early mature males, which had matured the previous autumn, were also tagged and released. To monitor migration of the fish, acoustic receivers were deployed along the migratory route. The proportion of S. salar that reached Lake Vänern was significantly greater for fish fed fat‐reduced feed than for fish given rations with higher fat content, regardless of ration size. Fish from the early mature male group remained in the river to a greater extent than fish from the three feeding regimes. Smolt status (degree of silvering), as visually assessed, did not differ among the feeding regime groups, and moreover, fully‐silvered fish, regardless of feeding regime, migrated faster and had a greater migration success than fish with less developed smolt characteristics. Also, successful migrants had a lower condition factor than unsuccessful ones. These results indicate that the migration success of hatchery‐reared S. smolts released to the wild can be enhanced by relatively simple changes in feeding regimes and by matching stocking time with smolt development.